Mechanostereochemistry and the mechanical bond - Barin, Gokhan (The Royal Society Publishing, 2012)
The chemistry of mechanically interlocked molecules (MIMs), in which two or more covalently linked components are held together by mechanical bonds, has led to the coining of the term mechanostereochemistry to describe a new field of chemistry that embraces many aspects of MIMs, including their syntheses, properties, topologies where relevant and functions where operative. During the rapid development and emergence of the field, the synthesis of MIMs has witnessed the forsaking of the early and grossly inefficient statistical approaches for template-directed protocols, aided and abetted by molecular recognition processes and the tenets of self-assembly. The resounding success of these synthetic protocols, based on templation, has facilitated the design and construction of artificial molecular switches and machines, resulting more and more in the creation of integrated functional systems. This review highlights (i) the range of template-directed synthetic methods being used currently in the preparation of MIMs; (ii) the syntheses of topologically complex knots and links in the form of stable molecular compounds; and (iii) the incorporation of bistable MIMs into many different device settings associated with surfaces, nanoparticles and solid-state materials in response to the needs of particular applications that are perceived to be fair game for mechanostereochemistry.